1996
DOI: 10.1002/(sici)1099-1522(199601)9:1<1::aid-pts349>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A review on modified atmosphere packaging and preservation of fresh fruits and vegetables: Physiological basis and practical aspects—part II

Abstract: Water‐soluble fluorescent Ag nanoclusters (see figure) are prepared by using star‐branched polyglycerol‐block‐poly(acrylic acid) (PG‐b‐PAA) templates. The dimensions of the clusters are conveniently controlled by the synthetic conditions. The “cage effect” associated with densely‐grafted PAA and the strong binding of protonated acrylic acid groups with Ag+ are two essential factors for the successful formation of the fluorescent nanoclusters, which exhibit remarkable photostability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 53 publications
0
33
0
1
Order By: Relevance
“…In the present study, the average RH and temperature of the evaporative cooler were 16.8°C and 78.8%, respectively, compared to 25.7°C and 43.0% at the ambient condition. This might have contributed to the high weight loss of papayas in the later storage condition which is associated with faster metabolism and ripening at higher temperature, increased cell wall degradation and higher membrane permeability leading to exposure of cell water for easy evaporation (Lee et al 1995).…”
Section: Treatmentsmentioning
confidence: 63%
See 1 more Smart Citation
“…In the present study, the average RH and temperature of the evaporative cooler were 16.8°C and 78.8%, respectively, compared to 25.7°C and 43.0% at the ambient condition. This might have contributed to the high weight loss of papayas in the later storage condition which is associated with faster metabolism and ripening at higher temperature, increased cell wall degradation and higher membrane permeability leading to exposure of cell water for easy evaporation (Lee et al 1995).…”
Section: Treatmentsmentioning
confidence: 63%
“…This might be attributed to reduced rate of respiration and transpiration of fruits due to relatively lower temperature and higher RH inside the evaporative cooler. Since a higher rate of respiration decreases shelf life (Lee et al 1995), the use of low temperature is indicated to be the most important means of extending the storage life of postharvest produce (Exama et al, 1993). Generally, the percentage marketability of papayas stored in the evaporative cooler was higher than those stored under ambient condition.…”
Section: Treatmentsmentioning
confidence: 99%
“…These factors explain the higher fresh weight losses in the present study in comparison to the observations of Maqbool et al (2010). Variations in these elements result in high weight losses of fruit setting off the formation of a water film on fruit surfaces that have a propensity to vaporize to a lower humidity environment and, above and beyond, easing spore germination to further invade tissues (CHITARRA; CHITARRA, 2005;LEE et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Modified atmosphere packaging (MAP) is derived from the idea that decreasing the respiration rate of agricultural products can extend their shelf lives (Lee et al, 1996;Rodriguez-Aguilera and Oliveira, 2009). Aging of fresh food constitutes an oxidative breakdown of the food substrates, and thus lower O 2 concentrations slow the oxidation rate and prolong the shelf life (Farber et al, 2003).…”
Section: Introductionmentioning
confidence: 99%